Branched PdAu nanowires with superior electrocatalytic formic acid oxidation activities. Issue 64 (21st August 2017) - Wang, Yingxia; Xiong, Zhong; Xia, Yanzhi
Abstract : Branched PdAu nanowires supported on graphene were prepared as catalysts for formic acid electro-oxidation, and they exhibited higher catalytic activity and durability than Pd/graphene and commercial Pd/C catalysts. Abstract : In this work, novel branched palladium–gold (PdAu) bimetallic nanowires supported on graphene (PdAu/graphene) were fabricated at relatively low temperatures for the first time by a one-pot co-reduction method with the aid of poly(diallyldimethyl-ammonium chloride). The structural characteristics of PdAu/graphene were confirmed by X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, high-angle annular dark-field scanning transmission electron microscopy and element mapping observations. The electrochemical properties of the PdAu/graphene were characterised by cyclic voltammetry and chronoamperometry (CA) in the formic acid oxidation reaction. Compared with a commercial Pd/C catalyst, the PdAu/graphene catalyst prepared in this work exhibited enhanced electrocatalytic activity including a higher oxidation current density, enhanced CO tolerance, and a more negative onset potential. Moreover, CA analyses demonstrated that PdAu/graphene shows higher stability than the Pd/C catalyst. The PdAu/graphene catalyst exhibited higher activity and strong poisoning resistance, which could be attributed to its special branched structure from PdAu nanowires.